2016
DOI: 10.1021/jacs.5b11892
|View full text |Cite
|
Sign up to set email alerts
|

α-Amino Aldehydes as Readily Available Chiral Aldehydes for Rh-Catalyzed Alkyne Hydroacylation

Abstract: Readily available α-amino aldehydes, incorporating a methylthiomethyl (MTM) protecting group on nitrogen, are shown to be efficient substrates in Rh-catalyzed alkyne hydroacylation reactions. The reactions are performed under mild conditions, employing a small-bite-angle bis-phosphine ligand, allowing for good functional group tolerance with high stereospecificity. Amino aldehydes derived from glycine, alanine, valine, leucine, phenylalanine, isoleucine, serine, tryptophan, methionine, and cysteine were succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…One approach to address this limitation has been to develop methods for the in situ removal, or derivatization of these substituents . Intermolecular hydroacylation methods based on S‐chelating substrates are some of the most general processes reported, with aryl‐, heteroaryl‐, alkenyl‐ and alkyl‐substituted aldehydes all proving to be excellent reaction partners . To extend the utility of these methods, our laboratory has shown that alkenyl‐ and aryl‐derived S‐chelating aldehydes are useful substrates for a series of tandem catalytic processes that deliver traceless hydroacylation products (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…One approach to address this limitation has been to develop methods for the in situ removal, or derivatization of these substituents . Intermolecular hydroacylation methods based on S‐chelating substrates are some of the most general processes reported, with aryl‐, heteroaryl‐, alkenyl‐ and alkyl‐substituted aldehydes all proving to be excellent reaction partners . To extend the utility of these methods, our laboratory has shown that alkenyl‐ and aryl‐derived S‐chelating aldehydes are useful substrates for a series of tandem catalytic processes that deliver traceless hydroacylation products (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…This observation is consistent with a serendipitous nding of a previous study from our laboratory. 22 The successful hydroacylation reactions with alkynol 2a conrmed the feasibility of a tandem hydroacylation/cyclisation protocol. Accordingly, we then set out to construct substituted alkynols, with the aim of achieving a diastereoselective cyclisation.…”
Section: O-and N-heterocyclesmentioning
confidence: 99%
“…All other solvents and reagents were purchase from Sigma-Aldrich Co. LLC, and used without further purification. The sphingosine 26 and azidosphingosine 27 were synthesized using literature procedures. All glassware utilized were flame-dried before use.…”
Section: Syn Thesismentioning
confidence: 99%